Web Service to Retrieve and Semantically Enrich Datasets for Theses From Open Educational Repositories - Maria Auxilio Medina Nieto; Paulo Daniel Vazquez Mora; Jorge De La Calleja Mora; Mireya Tovar Vidal; Eduardo Lopez Dominguez; Delia Arrieta Diaz; Ismael Everardo Barcenas Patino (IEEE Access, 2020)
The paper describes the design and implementation of a semantic web service that retrieves theses and extends the keyword based-search of a DSpace repository taking into account the roles of advisors and steering committee members formally represented into a custom-made ontology. The service uses SPARQL queries and the serialization module of RDF DSpace, this links the item submission process and the ontology, thus the more theses are added into a repository, the more instances are inserted into the ontology. The paper provides empirical insights about how to reuse theses metadata and includes the results of an exploratory and self-management survey of usability heuristic evaluation of a web site that enables to access the proposed service. Heuristics were estimated with a purposive sample of students, teachers, and managers, the results indicated a high satisfaction level and showed that the service increased theses accessibility in the web environment. The service also generates semantically enriched datasets that coexist with the repository, they are of utility and value to educational organizations as they give institutional visibility.